2016
DOI: 10.1007/s00246-016-1413-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Extracellular Matrix Patch and Standard Patch Material in the Pulmonary Arteries

Abstract: After pulmonary artery (PA) patch augmentation, surgical or catheterization reintervention to address PA stenosis is not uncommon. Multiple patch materials are available and the need for reintervention may be related to characteristics of the patch material. In this retrospective chart review of patients who underwent PA augmentation from 2004 through 2013, we compare outcomes after PA augmentation with standard patch (SP) material and extracellular matrix (ECM) patch material. The primary outcome was reinterv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…To estimate the early quality of PAR, we reviewed predominantly discharge echocardiography reports, as few other modalities were used prior to discharge. While we included this data (Table 1), and controlled for it in the multivariable analysis, we wish to note some caveats which likely limit the accuracy of the data: (1) only 51 preoperative sites were evaluated by angiography, CT, or magnetic resonance imaging; (2) We could not assign preoperative or postoperative degree of stenosis in 13 patients in the earlier era of the cohort (missing study reports); and 3) several cardiologists, each with some degree of subjective variation in estimating severity (particularly branch PA), read and reported results of the various studies. We therefore estimated degree of stenosis by using the qualitative language provided in the study reports and categorized as none to trivial, mild, moderate, or severe.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…To estimate the early quality of PAR, we reviewed predominantly discharge echocardiography reports, as few other modalities were used prior to discharge. While we included this data (Table 1), and controlled for it in the multivariable analysis, we wish to note some caveats which likely limit the accuracy of the data: (1) only 51 preoperative sites were evaluated by angiography, CT, or magnetic resonance imaging; (2) We could not assign preoperative or postoperative degree of stenosis in 13 patients in the earlier era of the cohort (missing study reports); and 3) several cardiologists, each with some degree of subjective variation in estimating severity (particularly branch PA), read and reported results of the various studies. We therefore estimated degree of stenosis by using the qualitative language provided in the study reports and categorized as none to trivial, mild, moderate, or severe.…”
Section: Data Collectionmentioning
confidence: 99%
“…Note that our most commonly used patch cost $5,100 more than our second most expensive patch. While clinical relevance may be questioned, a comparison of bovine pericardium to porcine submucosal patch, accounting for amount of patch material, yields costs of $28.4 per cm 2 for submucosal patch versus $20.3 per cm 2 for bovine pericardium.…”
Section: Primary Outcome: Reinterventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous small studies with shorter follow-up periods have shown similar, if not more favorable, results [ 12 , 13 , 21 , 39 , 40 ]. When compared directly to standard patch materials, including autologous pericardium, homograft and xenograft pericardium, and synthetic materials, no significant difference has been reported in outcomes for patients receiving CorMatrix™ patches [ 21 , 41 ]. Fraint et al compared CorMatrix™ patch patients ( N = 48) to a standard patch material cohort ( N = 173) composed of autologous pericardium, native PA tissue, non-native pericardial tissue, pulmonary and aortic homografts, and ePTFE [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…When compared directly to standard patch materials, including autologous pericardium, homograft and xenograft pericardium, and synthetic materials, no significant difference has been reported in outcomes for patients receiving CorMatrix™ patches [ 21 , 41 ]. Fraint et al compared CorMatrix™ patch patients ( N = 48) to a standard patch material cohort ( N = 173) composed of autologous pericardium, native PA tissue, non-native pericardial tissue, pulmonary and aortic homografts, and ePTFE [ 41 ]. This study demonstrated identical mortality rates of 6%, and total reintervention rates of 29% for CorMatrix™ as opposed to 39% for standard materials.…”
Section: Resultsmentioning
confidence: 99%